Barriers and Benefits of Quality Management System in Construction Industry of Pakistan - Muhammad Salman Khan Abbasi, Nafees Ahmed Memon, Tauha Hussain Ali, Shabir Hussain Khahro, Qasim Hussain Khahro (International Journal of Advanced Science and Technology, 2020)
In recent years the Construction Industry (CI) is becoming a global market in the world. This is one of the primary industries having a significant influence on the economy of the country. Pakistan is facing many issues related to the quality of the project, quality performance, and successful project delivery. To ensure successful projects delivery world-class construction companies are adopting Quality Management Systems (QMS) in their organization. The main focus of this study is to identify the benefits and barriers to implement QMS in their organizations. For this purpose, a questionnaire was designed after a detailed literature review and the data was collected from various ongoing projects of Pakistan. The study concludes that the construction companies are aware of the benefits of QMS implementation but still construction organizations are facing many barriers to implement QMS in their organizations. The study identifies that most significant barriers are Lack of interest from employees towards QMS implementation, Lack of qualified workforce for QMS implementation, Lack of initiative from company leadership.